Changes on Phosphorus Functional Fractions of Two Louisiana Alluvial Soils Grown with Corn at Different Phosphorus Rates. Issue 11 (17th June 2022) - Dalen, Marilyn; Tubana, Brenda; Teboh, Jasper; Kanke, Yumiko; Lofton, Josh
ABSTRACT: Soils in Mississippi River alluvial plains is one of the distinct soil areas in Louisiana under corn ( Zea mays ) production. This study was conducted to evaluate the changes on Mehlich-3 extractable-phosphorus (P) and P-functional fractions of two Louisiana alluvial soils i.e., Commerce silt loam (Commerce sl) and Perry clay (Perry cl). Potted air-dried soils were mixed with different P rates (0, 34, 67, 101 and 134 kg P2 O5 ha −1 ) and planted with corn seeds. Soil samples were collected 30 days after P application (30 DAP) and at harvest of corn. The Commerce sl and Perry cl differed considerably in the distribution of different P fractions. The unutilized P fertilizer was transformed into calcium (Ca)-P for Commerce sl while it transformed into iron (Fe)-P and reductant-P for Perry cl. Overall, the labile- and aluminum (Al)-P fractions before planting increased with increasing P rate while Fe-P with P rates increased only at harvest for both soils. With time across P rates, both soils built-up less readily available reductant-P. In terms of soil total P, residual-P and total inorganic P (Pi) components, Commerce sl and Perry cl soils differed significantly ( P < .05) at 30 DAP and at harvest. On the other hand, the total P and residual-P were not affected by P rates at 30 DAP and at harvest for both soils. Phosphorus fertilization depending on soil properties, can promote certain P fractions in the soil wherein the contribution to corn P nutrition would likely have to come from the readily available P fractions.